Land Trade and Development: A Market Design Approach - Gharad Bryan; Jonathan de Quidt; Tom Wilkening; Nitin Yadav (Center for Economic Studies and ifo Institute (CESifo), 2017)
Small farms and fragmented plots are hallmarks of agriculture in less-developed countries, and there is evidence of high returns to land consolidation and reallocation. Complementarities, holdout and asymmetric information mean that private trade will be slow to reallocate land, and imply that market design has the potential to contribute to the development process. Complexity concerns are, however, paramount. We present results from a framed field experiment with Kenyan farmers, comparing the performance of several continuous-time land exchanges. Farmers are able to achieve high degrees of efficiency, and to comprehend and gain from a relatively complicated package exchange.
Keywords: D47; C93; O13; Q15; 330; market design; field experiments; economic development; land trade